Effect of Herbal Liver Stimulants on Growth and Performance of Broiler Chicks - Somvanshi, S.P.S.; Gupta, Ramjee; Kaur, Navneet; Kumar, Aditya; Pandey, Nitin Kumar (Indian Journal of Extension Education, 2020)
The study was carried out on effect of herbal liver stimulants on growth and performance of broiler chicks. Hundred, one day old commercial broiler chicks were randomly selected. These were divided into four groups (G1, G2, G3, and G4) of 25 each. Treatment groups G2, G3, and G4 were provided 3ml, 6ml and 9 ml herbal liquid liver stimulant in drinking water per 25 chicks per day for 0-3 weeks on starter ration and 6ml, 9ml and 12ml herbal liquid liver stimulant per 25 chicks per day on finisher ration respectively, In the control group G1 no addition feed supplement given for 0-3 and 3-5 weeks. It was observed that growth rate, feed conversion efficiency, livability and dressing percentage were significantly higher in herbal liver stimulant feed supplemented groups compared to control. This indicates incorporation of herbal liver stimulant feed supplement in broiler ration level @ 9 ml/100 broiler chicks/day upto 0-3 weeks of age and @12 ml/100 broiler chicks/day 3-5 weeks of age is profitable in broiler production.
Keywords: Body weight gain; Broilers; Feed efficiency; Growth performance; Herbal liver stimulants; Herbs